Changes in bulk and rhizosphere soil microbial diversity communities of native quinoa due to the monocropping in the Peruvian Central Andes - Estrada Cañari, Richard (2023)
Quinoa (Chenopodium quinoa) is a highly nutritious crop that is resistant to adverse conditions. Due to the considerable increase in its commercial production in Andean soils, the plant is suffering the negative effects of monocropping, which reduces its yield. We used for the first time a high-throughput Illumina MiSeq sequencing approach to explore the composition, diversity, and functions of fungal and bacterial communities of the bulk and rhizosphere in soils of native C. quinoa affected by monocropping in the central Andes of Peru. The results showed that the bacterial and fungal community structure among the treatments was significantly changed by the monocropping and the types of soil (rhizosphere and bulk). Also, in soils subjected to monocropping, there was an increase in Actinobacteria and a decrease in Proteobacteria, and the reduction in the presence of Ascomycota and the increase in Basidiomycota. By alpha-diversity indices, lower values of bacteria and fungi were observed in the monoculture option compared to the soil not affected by monocropping, and sometimes significant differences were found between both. We detected differentially abundant phytopathogenic fungi and bacteria with growth-stimulating effects on plants. Also, we denoted a decrease in the abundance of the functional predictions in bacteria in the monocropped soils. This research will serve as a starting point to explore the importance and effects of microorganisms in degraded soils and their impact on the growth and quality of quinoa crops.